Rational synthesis and characterization of highly water stable MOF@GO composite for efficient removal of mercury (Hg2+) from water. Issue 10 (October 2022) - Fallatah, Ahmed M.; Shah, Habib Ur Rehman; Ahmad, Khalil; Ashfaq, Muhammad; Rauf, Abdul; Muneer, Muhammad; Ibrahim, Mohamed M.; El-Bahy, Zeinhom M.; Shahzad, Amir; Babras, Afshain
Abstract: The present study is aimed at adsorptive removal of Mercury (Hg 2+ ) using highly functionalized nanomaterials based on Graphene Oxide Zeolitic Imidazolate Framework composite (ZIF-67@GO). Solvothermal methodology was used to synthesize ZIF-67@GO composite. Synthesized compounds were confirmed by FTIR, SEM, PXRD and EDX analysis. The as-prepared ZIF-67@GO was tested as efficient adsorbent for effective removal of Mercury (Hg 2+ ) from aquatic environment. The atomic adsorption spectrophotometer was used to monitor the process of adsorption of Hg +2 on ZIF-67@GO. From the adsorption data, the maximum removal efficiency achieved was 91.1% using 10 mg amount of composite for 50 mL using 20 ppm Mercury (Hg 2+ ) solution. Different parameters like pH, contact time, concentration, adsorption kinetics and isotherm were also examined to explore adsorption process. Adsorption data fitted well for Freundlich Model having R 2 value of 0.9925 than Langmuir Isotherm with R 2 value of 0.9238. Kinetics were rapid and excellently described via 2nd order model with R 2 = 0.99946 than 1st order model with R 2 value of 0.8836. Freundlich and pseudo 2nd order models validated that multilayer chemisorption occurs during adsorption process due to the presence of highly functionalized sites on ZIF-67@GO composite. The synthesized composite material has shown excellent reusability. Thus, water stable ZIF-67@GO composites can efficiently be used for Mercury (Hg 2+ ) confiscation from water. Graphical abstract: Image 1 Abstract : Metal organic frameworks; Graphene oxide; Adsorption; Freundlich model; Langmuir model; Powdered X-ray diffraction.